2011
DOI: 10.1016/j.brat.2011.09.005
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of economic reasoning in hoarding disorder patients

Abstract: Current models of Hoarding Disorder (HD) emphasize problems of decision-making. Evidence for neuropsychological impairment in HD, however, has been mixed. The present study examined whether HD patients show problems of economic reasoning that could be associated with decision-making problems. Forty-two HD patients, 29 obsessive-compulsive disorder (OCD) patients, and 36 healthy control participants completed the Iowa Gambling Task (IGT), a computerized card playing game that assesses participants' ability to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 56 publications
2
23
0
Order By: Relevance
“…Lawrence et al (Lawrence et al, 2006) found evidence of a “link between hoarding and [increased] risky behavior on the IGT,” while the OCD group did not differ from controls. In contrast, neither Grisham et al (2007), nor Tolin and Villavicencio (2011) found that hoarding participants differed from controls on the IGT (Grisham et al, 2007; Tolin and Villavicencio, 2011). A large study by Mackin and colleagues found no differences between HD, OCD, or age matched controls on the IGT (Mackin et al, forthcoming).…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Lawrence et al (Lawrence et al, 2006) found evidence of a “link between hoarding and [increased] risky behavior on the IGT,” while the OCD group did not differ from controls. In contrast, neither Grisham et al (2007), nor Tolin and Villavicencio (2011) found that hoarding participants differed from controls on the IGT (Grisham et al, 2007; Tolin and Villavicencio, 2011). A large study by Mackin and colleagues found no differences between HD, OCD, or age matched controls on the IGT (Mackin et al, forthcoming).…”
Section: Introductionmentioning
confidence: 76%
“…Examining attitudes towards risk may be particularly fruitful in disorders hypothesized to be characterized by impulsivity, such as substance use disorders (SUD), as well as in those commonly regarded as excessively risk averse, such as obsessive-compulsive disorder (OCD) and hoarding disorder (HD). Current models of OCD and HD assert that both disorders involve impaired decision making (Cavedini et al, 2002; Grisham et al, 2010; Tolin and Villavicencio, 2011; Woody et al, 2014), and it has been suggested that abnormal attitudes towards uncertainty play a fundamental role in both (Admon et al, 2012; Grisham et al, 2010; Starcke et al, 2010; Zhang et al, 2015). In particular, the most prominent models of OCD and HD implicate excessive risk aversion and intolerance of uncertainty (Pushkarskaya et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Blom, Samuels, Grados, and Chen (2011) reported that HD participants performed better than OCD participants on the IGT, by learning faster and obtaining a greater overall net score. Tolin and Villavicencio (2011) found no difference between individuals with HD, non-hoarding OCD, and normal controls on the IGT, while Grisham et al (2007) found that HD participants had similar performance on the IGT compared to the non-hoarding OCD participants.…”
mentioning
confidence: 86%
“…The neurocognitive studies that do exist support the concept that executive dysfunction is a prominent feature of HD, although the data in specific cognitive domains (e.g., decision making, attention, etc.) are somewhat inconsistent …”
Section: Introductionmentioning
confidence: 99%
“…Most studies of executive function in HD have examined only one or a few cognitive domains (typically categorization, decision making, and speed of information processing) . In addition to the use of different cognitive measures across studies, even within the same cognitive domain, the subject populations (individuals with Obsessive Compulsive Disorder (OCD) and hoarding symptoms, and individuals with HD with or without OCD) also vary between studies, which could contribute to the inconsistency of findings.…”
Section: Introductionmentioning
confidence: 99%